2020
DOI: 10.1021/acs.jafc.0c01024
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Production of Lycopene from Corn Steep Liquor and Glycerol Using the Metabolically Engineered Deinococcus radiodurans R1 Strain

Abstract: Developing a highly efficient and ecofriendly system to produce desired products from waste can be considered important to a sustainable society. Here, we report for the first time high-yield production of lycopene through metabolically engineering an extremophilic microorganism, Deinococcus radiodurans R1, from corn steep liquor (CSL) and glycerol. First, the crtLm gene-encoding lycopene cyclase was deleted to prevent the conversion of lycopene to γ-carotene. Then, the crtB gene-encoding phytoene synthase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
1
28
1
Order By: Relevance
“…As can be seen in Figs. 2A and 2B, during the early exponential growth phase (12 h), lycopene content tended to rapidly increase up to 33.4 ± 1.3 mg/g DCW, but no significant increase was observed in the mid-exponential growth phase (24 h), which is consistent with our previous study [6]. In addition, the expression of the idi (isopentenyl diphosphate isomerase gene) and crtE (geranylgeranyl diphosphate synthase gene) genes, which encode the major rate-limiting enzymes in the carotenoid biosynthetic pathway [5,7,23], was lower at 24 h than at 12 h (Fig.…”
Section: Determination Uv Irradiation Onset By Comparative Analysis Osupporting
confidence: 91%
See 1 more Smart Citation
“…As can be seen in Figs. 2A and 2B, during the early exponential growth phase (12 h), lycopene content tended to rapidly increase up to 33.4 ± 1.3 mg/g DCW, but no significant increase was observed in the mid-exponential growth phase (24 h), which is consistent with our previous study [6]. In addition, the expression of the idi (isopentenyl diphosphate isomerase gene) and crtE (geranylgeranyl diphosphate synthase gene) genes, which encode the major rate-limiting enzymes in the carotenoid biosynthetic pathway [5,7,23], was lower at 24 h than at 12 h (Fig.…”
Section: Determination Uv Irradiation Onset By Comparative Analysis Osupporting
confidence: 91%
“…The extracts were analyzed using a high-performance liquid chromatography (HPLC) system (Agilent 1260 InfinityII, Agilent Corporation, USA) equipped with a Zorbax Eclipse XDB-C18 column (4.6 × 250 mm, Agilent, USA) as described previously [6].…”
Section: Methodsmentioning
confidence: 99%
“…We then overexpressed DXS in this strain, resulting in strain WT P-I-D, which was expected to increase the production of 1-deoxy- d -xylulose-5- phosphate (DXP) from pyruvate (Pyr) and 3-glyceraldehyde phosphate (GA3P), and thereby increase the flux through the non-mevalonate pathway. It has previously been shown that among the enzymes of this pathway, only overexpression of this enzyme can increase the production of GPP and carotenoids in D. radiodurans significantly [ 32 ], but in our experiments, it did not lead to a significantly higher pinene titer.…”
Section: Resultscontrasting
confidence: 73%
“…CSL is a major byproduct of cornstarch processing and is a low-cost source of proteins, amino acids, minerals and vitamins. It has been reported to be a potential nitrogen source for the production of bioproducts 36 39 . The optimized medium developed in this study (containing crude glycerol, CSL, and feed-grade l -tryptophan) was more cost-effective than other media and achieved high IAA production with a less-expensive fermentation medium.…”
Section: Discussionmentioning
confidence: 99%